2015
DOI: 10.13057/psnmbi/m010505
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of Selaginnela in the Provinve of Yogyakarta Special Region

Abstract: Abstrak. Setyawan AD, Sugiyarto, Susilowati A, Widodo. 2015. Keanekaragaman jenis dan sebaran Selaginella di Provinsi Daerah Istimewa Yogyakarta. Pros Sem Nas Masy Biodiv Indon 1: 987-992. Daerah Istimewa Yogyakarta memiliki topografi yang cukup beragam dengan ketinggian mulai dari tepian pantai hingga puncak Gunung Merapi (2930 m dpl). Sebagian besar wilayah Yogyakarta didominasi oleh kawasan perbukitan atau pegunungan yang relatif kering, yaitu: Pegunungan Kars Sewu, Pegunungan Menoreh dan Gunung Merapi. Dae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Moreover, AUC, just like Kappa, is reliable only if we use PA (Presence-Absence) model due to the fact that both AUC and Kappa are weighting omission and commission errors equally. Thus, in case of this study where presence-only data was used, AUC and Kappa are not necessarily reliable.According to Setyawan et al 2015, Selaginella is a herbaceous plant that will likely grow in the moist or rather wet region. Thus, since Java Island is a tropical island, elevation, which has a strong relationship with the level of humidity, plays another important role in the growth and the distribution of mountainous Selaginella.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AUC, just like Kappa, is reliable only if we use PA (Presence-Absence) model due to the fact that both AUC and Kappa are weighting omission and commission errors equally. Thus, in case of this study where presence-only data was used, AUC and Kappa are not necessarily reliable.According to Setyawan et al 2015, Selaginella is a herbaceous plant that will likely grow in the moist or rather wet region. Thus, since Java Island is a tropical island, elevation, which has a strong relationship with the level of humidity, plays another important role in the growth and the distribution of mountainous Selaginella.…”
Section: Discussionmentioning
confidence: 99%
“…is a single genus of ferns belong to Selaginellaceae family that lives in moist areas and is often found in highlands (Wijayanto 2014). Some species of Selaginella have a wide distribution and tend to be invasive, but the others are endemics, or even endangered according to IUCN criteria (Setyawan et al 2015). Studies on the diversity of this genus recorded a global distribution across several continents.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the predicted distribution of Selaginella plana's suitable habitat has almost the same pattern as the predicted suitable habitat for S. ciliaris. Several documents and studies had also reported the occurrence of S. plana in Vietnam (Spring 1843;Chang et al 2012), Cambodia (Spring 1843;Chang et al 2012), Myanmar (Chang et al 2012;Parveen et al 2017), Peninsular Malaysia and Singapore (Turner et al 1998;Chua et al 2005;Bedawi et al 2009), Philippines (Alston 1935;Zamora et al 1999;Tan 2013;De Guzman et al 2014), Sumatra (Sauerborn 2003;Beukema and Noordwijk 2004), Borneo (Said 2005;Ahmad and Holdsworth 2008;Komara et al 2016), Sulawesi (Mansur 2003; Hidayat 2011), Java (Rahayu et al 2012;Setyawan et al 2013;Setyawan et al 2015a;b;Setyawan et al 2016;Trimanto and Hapsari 2016), and Papua (Sambas et al 2003;Ebihara et al 2012;Johns et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The first source of locality points for both species was from field survey conducted in all Indonesian provinces in Java island between July 2007 and January 2014. The specimens were identified using several references on Selaginella of the Malay Archipelago and adjacent regions, both early (Alston 1934(Alston , 1935a(Alston ,b, 1937(Alston , 1940 and latest literature (Wong 1982(Wong , 2010Tsai and Shieh 1994;Li and Tan 2005;Chang et al 2012;Zhang et al 2013), as well as our previously publications (e.g., Setyawan 2012;Setyawan et al 2012Setyawan et al , 2013Setyawan et al , 2015aSetyawan and Sugiyarto 2015).…”
Section: Species Locality Datamentioning
confidence: 99%
“…Sindoro-Sumbing (Setyawan 2012), Mt. Merapi (Setyawan et al 2012(Setyawan et al , 2015a and Mt. Lawu (Setyawan et al 2013), and Dieng Plateau (Setyawan et al 2015c), but it is sometimes found in lower altitude (~ 500 m asl.…”
Section: Introductionmentioning
confidence: 99%